High stress related to COVID-19 among health workers in the Plateau Central healthcare region (BURKINA FASO): a cross-sectional study - Traoré, Solo; Dahourou, Désiré Lucien; Paré, Boyo Constant; Lompo, Yemboado Diedonné; Kaboré, Wendlassida Josiane; Ouédraogo, Wind-La-Sida Abd-El-Aziz; Kambou, Datouo Thomas; Salou, Wenddinda Rabbaly Adeline; Kaboré, Delphin; Ouédraogo, Abdoulaye; Sia, Siaka; Zorné, Mady; et al. (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic challenged the mental wellbeing of health workers. The objective of this study was to assess health workers' perceived stress during the response to COVID-19 in the Central Plateau region (Burkina Faso). Methods We conducted a cross-sectional study of health workers in the Central Plateau health region from September 20 to October 20, 2021. Agents' perceived stress was assessed by the Perceived Stress Scale (PSS-10). Factors associated with high stress (PSS-10 score ≥ 27) were identified by logistic regression. Results A total of 272 officers participated in the survey. The mean PSS-10 score was 29.3 points (standard deviation: 6.2). Three out of ten agents (68%) had a high level of stress. The main sources of stress were the risk of being exposed to contamination (70%) and being the source of contamination (78%). Working at the referral health center [adjusted odds ratio (aOR): 2.29; 95% confidence interval (95% CI): 1.19–4.41], the hospital as the main source of COVID-19 information (aOR: 1.17; 95% CI: 1.01-3.04), fear of COVID-19 patients being managed at one's center (aOR: 1.8; 95% CI: 1.06–3.07) were factors associated with high health worker stress levels during the first wave of COVID-19. Conclusion The COVID-19 pandemic caused high stress among health care workers in Burkina Faso. Psychological support for health center workers in responding to future epidemics would improve their mental health.